A New Xanthone from Garcinia oligantha and Its Cytotoxicity - Ye, Yan-Qing; Xia, Cong-Fang; Li, Xiang-Li; Qin, Yun-Hua; Du, Gang; Hu, Qiu-Fen; Gao, Xue-Mei (Asian Journal of Chemistry, 2014)
A new xanthone, methyl 6-(2-acetoxyethyl)-4,8-dihydroxy-9-oxo-9H-xanthene-1-carboxylate (1), was isolated from the stems of Garcinia oligantha. Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was tested for their cytotoxicities against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and it exhibited moderate cytotoxicity against NB4, PC3 and MCF7 cell with IC50 values of 6.2, 3.8 and 5.4 μM, respectively.